HAZARD SEISMIC ZONATION ANALYSIS OF WEST SUMATRA REGION USING PROBABILISTIC HAZARD SEISMIC ANALYSIS (PHSA) METHOD - Mudzullah Rajif; Syafriani Syafriani (PILLAR OF PHYSICS, 2021)
Indonesia is one of the countries that is prone to high intensity seismicity, where Indonesia is located between three main plates, namely the Eurasian plate in the north, the Indo-Australian plate in the south and the Pacific plate in the northeast. As a result of the meeting of the three plates, Indonesia has a high level of seismicity both on land and at sea. One of the provinces with a high level of earthquake hazard is West Sumatra. Seismic hazards are useful in designing earthquake-resistant buildings and can describe the effects of earthquakes at a location which will help in anticipating community preparedness and earthquake disaster mitigation efforts. This type of research is descriptive, namely by collecting catalog data for the NEIC / USGS earthquake with the period 1969-2019 with M ≥ 5 S.R. Seismic hazard data processing uses the probabilistic seismic hazard analysis (PSHA) method. PSHA is based on earthquake parameters that produce the greatest ground motion. The magnitude of the intensity at a location due to an earthquake in the earthquake source area with a magnitude M and a distance of R can be used as an attenuation function. The attenuation function used in this study is Joyner-Boore (1997) and Young et al (1997). The results show that the largest seismic hazard occurs in the PGA with a maximum range of 1.28 g - 3.69 g in the Mentawai Islands region. The seismic hazard level is in the Bukit Barisan area with a maximum PGA value of 1.72 g - 2.12 g.